Rapid reorganisation in the adult auditory system following unilateral deafening - Mossop, J; Jennifer E. Mossop (1999)
This thesis examines functional and neurochemical reorganisation within the adult mammalian inferior colliculus (IC) and primary auditory cortex (AI) following unilateral deafening. Contralateral cochlear ablation, either on the day of recording or at least three months prior, caused an increase in the proportion of IC recording sites excited by acoustic stimulation of the ipsilateral ear in the adult ferret. In the gerbil IC, these changes occurred within minutes of contralateral cochlear ablation. Likewise, in ferret AI, contralateral cochlear ablation could produce a dramatic and rapid expansion of the cortical area that was excited by ipsilateral acoustic stimulation. In both gerbil IC and ferret AI, significant changes in other response properties were not generally observed between multiple-unit recordings made before and after acute cochlear ablation. Areas of emergent excitation (excited post-ablation but not pre-ablation) displayed normal tuning and response properties, implying the existence of apparently normal, but unexpressed ipsilateral excitatory connections in the IC and AI of pre-ablation animals. A rapid unmasking mechanism, involving release from spontaneously-driven contralateral inhibition, is proposed. A reduction of inhibition on a longer time scale (4-24 hours) is suggested by an observed reduction in glutamic acid decarboxylase in the adult gerbil IC contralateral to the ablated ear. Optical imaging of intrinsic signals was pioneered as a technique for examining functional organisation in ferret AI, and several protocol improvements were found for imaging normal ferret AI. However, an unforseen influence of vascular noise upon the small ipsilateral optical signal made pre- and post-ablation image comparisons difficult to interpret. Overall, the experimental work presented here shows that the adult auditory system, like other mature sensorimotor systems, is capable of rapid functional reorganisation. The most rapid changes appear to be mediated by unmasking of previously inhibited connections.